Suspended structure behind electric motorcycle car - ZHAO XIAOYONG (2016)
The utility model discloses a suspended structure behind electric motorcycle car, hang main part and bumper shock absorber fixed establishment, its characterized in that after, including frame Assembly: after hang that the main part includes two parallel arrangement and through connecting piece installation bottom sprag roof beam as an organic whole, bottom sprag roof beam one end hinges on frame Assembly through the pivot, and the slope of the one end of two bottom sprag roof beams is provided with a U type bent beam, and the articulated department of hanging the main part at two bottom sprag roof beams after with is respectively fixed through a main tributary supporting beam in U type bent beam top both sides, bumper shock absorber fixed establishment is installed at U type bent beam top, transversely be provided with the bumper shock absorber between bumper shock absorber fixed establishment and the frame Assembly. The utility model discloses an optimize back suspended structure, alleviate frame Assembly w